ANALYSIS OF THE EFFECT OF PROFITABILITY, SOLVENCY, CORPORATE SOCIAL RESPONSIBILITY ON EARNINGS MANAGEMENT IN MANUFACTURING COMPANIES - Sutri Handayani; Dyah Ayu Ambarrini; Mohammad Syafik (Jurnal Scientia, 2022)
This study aims to determine the effect of profitability, solvency and Corporate Social Responsibility on earnings management. This research uses quantitative methods. The population in this study were all manufacturing companies listed on IDX in 2018-2020, totaling 542 companies. The sampling technique used was purposive sampling and resulted in 15 companies being selected as samples with a total of 38 data. This study uses secondary data. The results show that profitability has a positive and significant effect on earnings management, solvency has a positive and significant effect on earnings management, and Corporate Social Responsibility has no effect on earnings management. Simultaneously profitability, solvency, Corporate Social Responsibility affect earnings management.